External validation of models predicting the individual risk of metachronous peritoneal carcinomatosis from colon and rectal cancer. (April 2016) - Segelman, J.; Akre, O.; Gustafsson, U. O.; Bottai, M.; Martling, A.
Abstract: Aim: To externally validate previously published predictive models of the risk of developing metachronous peritoneal carcinomatosis (PC) after resection of nonmetastatic colon or rectal cancer and to update the predictive model for colon cancer by adding new prognostic predictors. Method: Data from all patients with Stage I–III colorectal cancer identified from a population‐based database in Stockholm between 2008 and 2010 were used. We assessed the concordance between the predicted and observed probabilities of PC and utilized proportional‐hazard regression to update the predictive model for colon cancer. Results: When applied to the new validation dataset ( n  =   2011), the colon and rectal cancer risk‐score models predicted metachronous PC with a concordance index of 79% and 67%, respectively. After adding the subclasses of pT3 and pT4 stage and mucinous tumour to the colon cancer model, the concordance index increased to 82%. Conclusion: In validation of external and recent cohorts, the predictive accuracy was strong in colon cancer and moderate in rectal cancer patients. The model can be used to identify high‐risk patients for planned second‐look laparoscopy/laparotomy for possible subsequent cytoreductive surgery and hyperthermic intraperitoneal chemotherapy.